Clinical impact of dual red imaging in colorectal endoscopic submucosal dissection: a pilot study. (September 2016) - Ninomiya, Yuki; Oka, Shiro; Tanaka, Shinji; Hirano, Daiki; Sumimoto, Kyoku; Tamaru, Yuzuru; Asayama, Naoki; Shigita, Kenjiro; Nishiyama, Soki; Hayashi, Nana; Chayama, Kazuaki
Background: Dual red imaging (DRI), a novel image-enhanced endoscopic technique, is expected to improve visibility of thin vessels, but no reports of the clinical use of DRI in colorectal endoscopic submucosal dissection (ESD) have been published. We aimed to compare the visibility of vessels, demarcation line between the submucosal and muscle layers after injection of hyaluronate sodium with minute indigo carmine, and fibrosis on DRI with that on white light imaging (WLI). We applied the principle of DRI to the image of the submucosal layer during colorectal ESD as a pilot study. Methods: A total of seven physicians compared 17 DRI images to the corresponding WLI images in colorectal ESD. The physicians compared the number of arteries identified on DRI with the actual number of arteries. The physicians rated the visibility of vessels, the demarcation line between the submucosal and muscle layers after injection of hyaluronate sodium with minute indigo carmine, and fibrosis. Inter-observer agreement was also examined using the kappa statistic. Results: Visibility of vessels and the demarcation line between the submucosal and muscle layers after injection of hyaluronate sodium with minute indigo carmine improved with the use of DRI compared with that using WLI. DRI can discriminate between arteries and veins clearly through the color of the vessels. Conclusions: DRI improves the visibility of vessels, especially that of arteries, as they appear orange, and the demarcation line of the muscle layer. DRI may help to make colorectal ESD safer and faster.